Arsenic exposure analysis for children living in central China: From ingestion exposure to biomarkers. (January 2022) - Wang, Beibei; Cheng, Hongguang; Lin, Chunye; Zhang, Xuan; Duan, Xiaoli; Wang, Qin; Xu, Dongqun
Abstract: Emerging evidence indicates that chronic low-dose arsenic (As) exposure can pose adverse health effects to children. This study aimed to systematically study the exposure risk induced by As ingestion in children living in Hubei Province, central China. The feasibility of first morning spot urine instead of 24-h urine as an environmental exposure biomarker was also explored. A total of 120 children aged 2–17 years were recruited from an urban area for the collection of biomarker samples (first morning and 24-h urine samples), environmental exposure samples (duplicate diets, drinking water, and soil), and related child-specific exposure factors. The external exposure risk, internal exposure level, and source of exposure to As in children were analyzed. The results indicated that As concentration in duplicated diets, water, and soil were 29.2 μg kg −1, 1.3 μg L −1, and 9.3 mg kg −1, respectively; these were all below the corresponding maximum allowable levels in China (the threshold value of As in most food, drinking water and soil are 0.5 mg⸱kg −1, 0.01 mg L −1, and 20 mg⸱kg −1, respectively). Dietary intake was the predominant exposure route, accounting for 90% of the total daily dose. The combined oral non-carcinogenic and carcinogenic risks all exceeded the corresponding maximum acceptable risk level. Therefore, As bioavailability should be investigated and used in health risk assessment. Multiple linear regression analysis indicated that urinary As was positively associated with dietary As, with a one-unit increase in daily As intake from the diet associating with 4.82 and 5.21 μg g −1 increases in 24-h urine and first morning urine, respectively. Furthermore, significant correlations with 24-h urine and external exposure metrics suggested that creatine-adjusted As concentrations in first morning urine could be an appropriate substitute of 24-h urine as exposure biomarkers. Graphical abstract: Image 1 Highlights: Arsenic exposure health risk for general children in the study area exceeded 10 −6 . Arsenic bioavailability in diet should be considered in health risk assessment. Arsenic level in 1st morning & 24-h urine averaged 15.5 & 11.4 μg/L, respectively. Arsenic level in 1st morning & 24-h urine increased by 5.2 & 4.8 μg/g per unit increase in daily As intake, respectively. Creatine-adjusted As level in 1st morning urine can be used as exposure biomarker.